Hybrid fiber-reinforced polymer structural frames with ductile gusset connections: a new paradigm in structural design - Thongchom, Chanachai; Ghamari, Ali; Putra Jaya, Ramadhansyah (Elsevier Ltd, 2026)
Although Fiber Reinforced Polymer (FRP) offers significant advantages, it exhibits low ductility. Consequently, FRP is unsuitable for primary elements in Moment Resisting Frames (MRFs), where plastic hinges form at beam ends. To address this limitation, this paper proposes a novel ductile MRF system employing pultruded I-shaped FRP profiles as beams and columns, joined by replaceable ductile steel gusset plates designed to facilitate controlled plastic hinge development within the connections. This approach intentionally confines ductility to the gusset plates, ensuring FRP members remain elastic to enhance durability and efficiency. Comprehensive finite element modeling and parametric studies assess the effects of gusset thickness, length, slenderness, and stiffener arrangement on critical seismic performance indicators, including stiffness, capacity, ductility, yield displacement, and energy dissipation. Findings reveal that optimally designed gusset plates yield stable hysteresis loops without degradation and adequate ductility. By increasing the length and thickness of the gusset plate, the capacity and stiffness are enhanced although the length is more effective than thickness. Accordingly, adding stiffeners to models increase the stiffness by 1% to 26%. Also, for the long gusset plate, adding the stiffeners cause to increase the ductility between 12% and 46% that is considerable. Referring the mentioned finding, adding the stiffeners are strongly recommended. Corresponding design equations for the system are provided that enable the practical design of system with predictable behavior.